The Meaning and Strategies of Patience Among Professionals in the Autism Service Center of Riau Province - Ahmad Hidayat; Sigit Nugroho; Lisfarika Napitupulu; Wina Diana Sari (Institute of Multidisciplinary Research and Community Service, 2026)
Patience is an essential competency for professionals working with children with autism. This study aimed to explore the meaning and strategies of patience among professionals at the Autism Service Center of Riau Province, Indonesia. A qualitative phenomenological design was employed, involving four purposively selected participants representing integrated therapy, transition class, and health services. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings revealed that patience was understood as a hierarchical psychological construct consisting of five interconnected themes: self-control, resilience, endurance, tawakal (trustful surrender to God), and self-acceptance. The findings further indicated a developmental trajectory from emotional regulation toward existential acceptance, with self-acceptance representing the highest level of patience. Patience strategies varied according to service-unit demands. Integrated therapy emphasized understanding children’s specific disorders and gratitude; transition-class services applied deep-breathing relaxation and self-affirmation; while health services relied on continuous updates in knowledge about autism. Several transversal strategies were identified across units, including daily emotional management, acceptance of limitations, and ongoing self-reflection. Due to the limited, exploratory sample, these findings cannot yet be generalized to all autism service professionals in Indonesia. Theoretically, this study enriches the psychological framework of patience by integrating cultural-religious dimensions such as tawakal and by indicating that emotional suppression may function adaptively within autism-service contexts. In practice, the findings suggest the importance of context-specific patience training programs for autism service professionals.Keywords: patience; autism; professional; patience strategy; phenomenology.